Subtitles as a Tool to Boost Language Learning and Intercultural Awareness? : Children’s Views and Experiences of Watching Films and Television Programmes in Other Languages with Interlingual Subtitles - Black, Sharon (Journal of Audiovisual Translation, 2022)
There is growing concern about the steep decline in language learning in the UK over the last 20 years. A simple, inexpensive way to boost children’s learning of other languages in the UK and indeed in other countries could be to increase their exposure to subtitled audiovisual (AV) content in other languages. There is considerable evidence that subtitled AV content can aid children’s acquisition of other languages, enhance their literacy skills, and foster intercultural awareness. However, little attention seems to have been paid thus far to eliciting the opinions and experiences of children themselves of watching subtitled films and television programmes in other languages. This study aims to contribute to filling the gap. A cohort of 17 children aged 8-9 years took part in interviews and participatory workshops and shared their views and experiences of viewing AV content with interlingual subtitles. Although the sample size is small, the findings of this study support the proposal of providing children with greater access to subtitled AV content in other languages, since the children’s responses to the idea were overwhelmingly positive, and many felt that this would help them to learn languages and about other cultures in a fun way. Lay summary In the UK, the number of children and young people studying languages has fallen sharply over the last 20 years. This is causing a lot of concern, because learning other languages is very beneficial, especially for children and young people. Studying languages can improve their communication skills and open up other cultures and job opportunities to them. Language skills are also important for inclusion and wellbeing in our increasingly multilingual societies and for international relations and trade. Many studies have shown that watching videos in other languages with subtitles can boost children’s language learning and help them learn to read in their home language. But few researchers have asked children themselves about their opinions on reading subtitles. To help fill this gap, I held interviews and workshops with 17 children aged 8–9 years about their views and experiences of watching subtitled videos in other languages. Their answers were very positive. Many felt it helps them learn languages and about other cultures in a fun way. As a result, I have concluded that a cheap, simple way we can help children to learn other languages is by making it easier for them to watch more TV programmes and films in other languages with subtitles.